2000
DOI: 10.1046/j.1523-1747.2000.00038.x
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Immunization Indicates that CD8+ T Cells are the Dominant Effector Cells in Trinitrophenyl-Specific Contact Hypersensitivity

Abstract: The identity of the effector T cell population involved in contact hypersensitivity is still questionable with evidence promoting both CD4+ or CD8+ T cells. Previous experimental studies have relied on the in vivo depletion of T cell subsets using antibody, or the use of knock-out mice with deficiencies in either CD4+ or CD8+ T cell-mediated immunity. To address the role of the class I- and class II-mediated pathways of T cell activation in contact hypersensitivity responses in mice with an intact immune syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 24 publications
3
61
0
2
Order By: Relevance
“…To address this knowledge gap, we sought to determine the effects of cell type-specific p38α deficiency on contact hypersensitivity (CH). In this skin immune reaction, topical contact with a small-molecule allergen (hapten) leads to a priming of specific T cells (sensitization phase); the resulting effector T cells, particularly CD8 + effectors (12)(13)(14)(15), are recruited to and activated in the skin upon reencounter with the hapten, a process associated with actual skin disease (challenge phase).…”
Section: Resultsmentioning
confidence: 99%
“…To address this knowledge gap, we sought to determine the effects of cell type-specific p38α deficiency on contact hypersensitivity (CH). In this skin immune reaction, topical contact with a small-molecule allergen (hapten) leads to a priming of specific T cells (sensitization phase); the resulting effector T cells, particularly CD8 + effectors (12)(13)(14)(15), are recruited to and activated in the skin upon reencounter with the hapten, a process associated with actual skin disease (challenge phase).…”
Section: Resultsmentioning
confidence: 99%
“…The implication is that CD4 π effector cells mediated the response. In contrast, however, when the same peptides were administered to mice in the context of DC, then only class I-binding TNP-peptides induced contact hypersensitivity, and of a magnitude comparable with that observed following conventional topical sensitization (32). The important conclusions that can be drawn from these experiments are that CD8 π may be potent effectors of contact hypersensitivity, but that CD4 π may be active also, and the way in which the inducing antigen is delivered to the immune system (presumably related to the mechanism of MHC loading) can have an important influence on whether CD8 π or CD4 π T lymphocytes predominate as effector cells.…”
Section: Cd8 π Effector Cells and Interplay With Cd4 π Cellsmentioning
confidence: 85%
“…This is despite the fact that in some cases it appears possible to generate CD8 π T lymphocyte responses to skin sensitizing chemicals in the absence of antigen-activated CD4 π cells (28,31). In this context, an investigation of CD4 π /CD8 π selectivity for contact hypersensitivity conducted in immunologically intact mice is instructive (32). Trinitrophenyl (TNP)-derivatized peptides that have affinity for either class I or class II MHC molecules were used.…”
Section: Cd8 π Effector Cells and Interplay With Cd4 π Cellsmentioning
confidence: 99%
“…This work demonstrated that the CD4 + T cell population critical for the initiation of a CS response represents only a small proportion of the total number of adherent leukocytes in the inflamed dermal microvasculature. However, CD8 + T cells have also been shown to play important effector roles in CS (40,41). Therefore, in this study we used this approach to examine adhesion of CD8 + T cells in addition to CD4 + T cells and neutrophils in the two-challenge CS model ( Fig.…”
Section: Neutrophil and Cd8 + T Cell Adhesion Are Blunted In Multiplementioning
confidence: 99%